Junctional Ectopic Tachycardia after Complete Repair of Tetralogy of Fallot in Children less than 1 Year - A. Petrenko; E. Yakimishin; S. Boyko (Ukrainian Journal of Cardiovascular Surgery, 2019)
Junctional ectopic tachycardia (JET) is frequent acceleration of rhythm after complete repair of Tetralogy of Fallot. JET is associated with prolongation of been in the ICU and worsening of the prognosis. The present ways of preventing of JET cannot be routinely applied for all patients, so it needs to identify patients with high risk of JET emergence.Purpose. It needs to analyze cases of JET and identify risk factors for patients requiring Tetralogy of Fallot complete repair.Methods and materials. It was analyzed 81 patients with Tetralogy of Fallot after complete repair from 2014 until 2019 in National Amosov Institute of Cardiovascular Surgery.Results and discussion. Post-operative analysis shows that magnesium and potassium levels in blood were lower in patients with JET than in patients without JET (0.9 ± 0.41 and 1.14 ± 0.43, respectively, p < 0.05). Patients with JET were younger (7.8 ± 1.4 and 9.9 ± 1.6, respectively, p < 0.05), had lower body weight (8.1 ± 1.0 and 9.3 ± 0.9, respectively, p < 0.05) and higher heart rate in the pre-operative period (147.6 ± 11.4 and 124.9 ± 13.9, respectively, p < 0.05). It was found out that pre-operative respiratory cyanotic attacks are independent risk factors for JET. During the work we also found that the administration of beta-blockers in the pre-operative period significantly reduces the JET development (4 (26.6%) and 27 (40.9%) respectively, p <0.05).Conclusion.Younger age, lower body weight, and respiratory cyanotic attacks in the pre-operative period are unadjusted risk factors of the JET development in the early postoperative period. Blood magnesium and potassium concentrations are correlated factors in the JET development. Beta-blockers may be recommended for the prevention of JET in the early post-operative period in patients who have risk factors.